The Implementation of Differentiated Learning with a Problem-Based Learning Model to Enhance Learning Outcomes in Pancasila Education Subject - Nurohmasari, Maria Lusiana; Hanif, Muhammad; Pribadi, Dwi Bambang Tulus (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2024)
This study examines the effect of implementing differentiated learning with the Problem-Based Learning model on students' learning outcomes in the Pancasila Education subject. The method employed in this research is classroom action research involving 25 Grade VII-F students at SMPN 6 Madiun. The study was conducted over two cycles, each comprising the stages of planning, implementation, observation, and reflection. The research results were analyzed using simple quantitative techniques to evaluate learning outcomes and the percentage of student mastery. The findings indicate that implementing differentiated learning with the Problem-Based Learning model in the Pancasila Education subject effectively improved students' learning outcomes. This was demonstrated by the increase in the percentage of student mastery across the cycles. Pre-cycle data showed that only 24% of students achieved mastery. After the intervention, student mastery increased to 52% in the first cycle and 84% in the second cycle.